Ocular adverse events associated with antibody-drug conjugates in oncology: a pharmacovigilance study based on FDA adverse event reporting system (FAERS) - Mao, KaiLi; Chen, Ping; Sun, HuaYu; Zhong, SongYang; Zheng, HongLiang; Xu, LuYao (Frontiers in Pharmacology, 2024)
Background: Antibody-drug conjugates (ADCs) have emerged as the focus and hotspots in the cancer field, yet the accompanying ocular toxicity has often been underestimated. We aimed to comprehensively and comparatively analyze the risk of ocular toxicity associated with various ADCs using the FDA Adverse Event Reporting System (FAERS) database.Methods: Data were extracted from the FAERS database from Q3 2011 to Q3 2023.We analyzed the clinical characteristics of ADCs-related ocular adverse events (AEs).These data were further mined by proportional analysis and Bayesian approach to detect signals of ADCs-induced ocular AEs. Moreover, the time to onset of ocular toxicity was also evaluated.: A total of 1,246 cases of ocular AEs were attributed to ADCs. Ocular toxicity signals were observed in patients treated with belantamab mafodotin, brentuximab vedotin, enfortumab vedotin, mirvetuximab soravtansine, sacituzumab govitecan, trastuzumab deruxtecan, and trastuzumab emtansine. Of these, belantamab mafodotin, trastuzumab emtansine, and mirvetuximab soravtansine, whose payloads are microtubule polymerization inhibitors, were more susceptible to ocular toxicity. The ten most common ADCs-related ocular AEs signals are keratopathy [ROR = 1,273.52, 95%CI (1,129.26~1,436.21)], visual acuity reduced [ROR = 22.83, 95%CI (21.2~24.58)], dry eye [ROR = 9.69, 95%CI (8.81~10.66)], night blindness [ROR = 259.87, 95%CI (228.23~295.89)], vision blurred [ROR = 1.78, 95%CI (1.57~2.02)], photophobia [ROR = 10.45, 95%CI (9.07~12.05)], foreign body sensation in eyes [ROR = 23.35, 95%CI (19.88~27.42)], ocular toxicity [ROR = 144.62, 95%CI (117.3~178.32)], punctate keratitis [ROR = 126.21, 95%CI (101.66~156.69)], eye disorder [ROR = 2.71, 95%CI (2.21~3.32)]. In terms of onset time, sacituzumab govitecan displayed an earlier onset of 21 days, while trastuzumab deruxtecan exhibited the latest onset of 223 days. Conclusion: ADCs may increase the risk of ocular toxicity in cancer patients, leading to serious mortality. With the widespread application of newly launched ADCs, combining the FAERS data with other data sources is crucial for monitoring the ocular toxicity of ADCs. In addition, novel ocular toxicity signals not documented in product labeling were detected. Further research will be necessary to validate our 2 findings in the future.